2020
DOI: 10.31729/jnma.4995
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Health Care Professionals and Medical Students Regarding Covid-19 in a Tertiary Care Hospital in Nepal

Abstract: Introduction: The lack of knowledge among health care professionals leads to diagnostic delays,further spread of disease, and poor infection control practices. Health care professionals must beupdated knowledge regarding COVID-19. This study aims to assess the knowledge of health careprofessionals regarding COVID -19 in a medical college in Chitwan. Methods: A Knowledge, Attitude and Practice Study was carried out in a tertiary care hospitalin Chitwan, Nepal from April 22, 2020, to April 28, 2020. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…The finding is different from a study conducted by Neupane et al on health care professionals and medical students shows that 58% of the study population had good knowledge and 22.7% had fair knowledge and remaining had poor knowledge. 7 The difference existed because of the structure of questionnaire used, with our study including very basic questions tailored to general population compared to the questions used in aforementioned study. Besides, that study used Multiple Choice Questions (MCQs) to determine knowledge, which we did not use.…”
Section: Discussionmentioning
confidence: 99%
“…The finding is different from a study conducted by Neupane et al on health care professionals and medical students shows that 58% of the study population had good knowledge and 22.7% had fair knowledge and remaining had poor knowledge. 7 The difference existed because of the structure of questionnaire used, with our study including very basic questions tailored to general population compared to the questions used in aforementioned study. Besides, that study used Multiple Choice Questions (MCQs) to determine knowledge, which we did not use.…”
Section: Discussionmentioning
confidence: 99%
“…34 As such, periodic educational interventions and training programmes regarding infection control practices for COVID-19 must be implemented among all HCWs, especially those who encounter new emerging infectious diseases. 35 In the practice domain, education level had the highest influence on the ability of HCWs to implement the prevention and control of HAIs. Other positive factors included gender, occupational exposure within the previous 6 months, authority to perform invasive operations, antibacterial drug training and attendance of clinical consultations.…”
Section: Open Accessmentioning
confidence: 99%
“…The average score of the individuals in the study group (11.9) (27). The frequency of positive attitudes among HCP in Nigeria had been reported as 64% (26). In this study, those with university and higher education level demonstrated more positive attitude than those with high school and associate education level.…”
Section: Discussionmentioning
confidence: 52%
“…Another study conducted in Uganda; it was reported that 69% of the HCP had sufficient knowledge level (25). In a study executed with HCP in Nepal, it was reported that good knowledge level was found with a frequency of 82.2% (26,27). The study conducted by Ayinde et al among HCP in Nigeria the frequency of good knowledge was reported as 78.6% (28).…”
Section: Discussionmentioning
confidence: 94%